Occurence of infectious bovine rhİnotracheİÜs after pasîeurella haemolytica vaccinations - İrem Gütaçtı; Hakan Bulut (Eurasian Journal of Veterinary Sciences)
Pasteurella (Mannheimia) haemolytica is one of the major causative agents of severe pneumonia causing high mortality rate in cattle. Vaccines for pneumonic pasteurellosis have been used in many countries. In this study, infectious bovine rhinotracheitis (IBR) cases occuring after Pasteurella haemolytica vaccination were reported. For this aim, nasal swap samples were taken from 10 IBR-suspected animals lhat were previously vaccinated against Pasteurella haemolytica. In result of polymerase chain reaction (PCR), 6 of 10 IBR-suspected animals were detected as positive. Considering high prevalance of IBR infection in our country, results of this study is very important.